2018
DOI: 10.1155/2018/2618071
|View full text |Cite
|
Sign up to set email alerts
|

T118M Variant of PMP22 Gene Presents with Painful Peripheral Neuropathy and Varying Charcot-Marie-Tooth Features: A Case Series and Review of the Literature

Abstract: The clinical effect of T118M variant of the PMP22 gene has been controversial. Several studies have suggested that it may be autosomal recessive, partial loss of function, or a benign variant. Here we report three cases in further support that the T118M variant of the PMP22 gene is a partial loss of function variant. These three unrelated cases were heterozygotes with the T118M variant of the PMP22 gene. All three cases presented with painful peripheral neuropathy and varying degrees of Charcot-Marie-Tooth exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The ACG→ATG missense mutation in the codon of PMP22 that encodes the T118M amino acid variation ( Fig. 1 ) is unusual among known PMP22 disease mutations in that it does not seem to be 100% penetrant when expressed under heterozygous WT/mutant conditions ( 16 , 17 , 18 , 19 ). Some heterozygous carriers do not present with CMT or related peripheral neuropathies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ACG→ATG missense mutation in the codon of PMP22 that encodes the T118M amino acid variation ( Fig. 1 ) is unusual among known PMP22 disease mutations in that it does not seem to be 100% penetrant when expressed under heterozygous WT/mutant conditions ( 16 , 17 , 18 , 19 ). Some heterozygous carriers do not present with CMT or related peripheral neuropathies.…”
mentioning
confidence: 99%
“…On the other hand, some do, usually with relatively mild neuropathy. Studies of nerve conduction velocities in heterozygous human subjects have found that some individuals have moderately decreased conduction velocity, whereas others exhibit normal conduction velocities ( 16 , 18 , 19 ). It should be added that the very rare homozygous (T118M/T118M) individuals present with much more severe neuropathy ( 18 ) and that also-rare T118M/null patients exhibit more severe neuropathy than WT/null individuals ( 20 ).…”
mentioning
confidence: 99%
“…In addition, four out of the five individuals had electrodiagnostic testing performed. Genetic testing for inherited neuropathies was performed through Invitae (San Francisco, CA) [ 12 ]. Three pathogenic variants in the GDAP1 gene were identified, and one variant of uncertain significance in the GDAP1 gene was also detected.…”
Section: Methodsmentioning
confidence: 99%